Autosexual behavior as a topic for inclusion in gynecological practice - Ewa Jakubek; Grażyna Jarząbek-Bielecka; Jacek Boroch; Małgorzata Mizgier; Katarzyna Plagens-Rotman; Witold Kędzia (IMR Press, 2021)
It is advisable that the medical history of the gynecologist be extended to include the functioning of patients in the sexual sphere, including partner relationships, which affects health, including women's sexual health. For many patients, sexology issues are taboo and autosexual behavior (masturbation) is a special taboo. Masturbation refers to sexual stimulation, especially of one's own genitals and often to the point of orgasm, which is performed manually, by other types of bodily contact (except for sexual intercourse), by use of objects or tools, or by some combination of these methods. Autosexual behavior as a topic for inclusion in general gynecology and developmental gynecology indicates the need for a very individual approach to this issue in the context of a given patient. Similar medical issues seem to refer to a general truth about medicine that it is neither merely art nor science, in the modern sense of these terms. It is a separate, indirect field, tertium quid, i.e., the third, intermediate possibility between art and science, but different from both. In the Aristotelian sense, medicine is a habit of practical understanding, perfected by experience in patient care, and the issue of autosexual behavior in general gynecological requires special experience and an individual approach to a patient.